The Role of Social Media in Shaping Public Trust in Government Institutions - Putri, Aprilia (Indonesian Journal of Research and Service Studies, 2024)
The rapid expansion of social media has transformed government communication and significantly impacted public trust in government institutions. However, previous studies have produced fragmented findings regarding the mechanisms by which social media shapes institutional trust. This study aims to analyze the role of social media in fostering public trust in government institutions and to identify key factors underlying this relationship through a comprehensive literature synthesis. This research employs a qualitative literature review approach by systematically analyzing recent publications retrieved from major academic databases using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. The findings indicate that social media strengthens public trust by increasing transparency, improving the quality of digital communication, and encouraging citizen participation, while misinformation remains a key challenge that can undermine institutional credibility. The study concludes that effective, transparent, and participatory digital communication is crucial for strengthening public trust and provides a conceptual foundation for future research on digital governance and government communication.